The Significance of Blockchain Implementation in the Issuance of Land E-Certificates: Examples from Ghana and Germany (Lex localis - Journal of Local Self-Government, 2023)
Indonesia has established regulations on the implementation of land e-certificate. Unfortunately, the policy has not been able to provide real protection for the people, in this case the holders of land rights and other interested parties. This study aims to analyze the significance of the blockchain implementation as a security system for land e-certificate that generate further implications such as the ease of doing business and investment index. This study is a legal study with comparative approach. The comparison used cases of Ghana and Germany as examples. The results of the study show that Indonesia should create a blockchain system, like in Germany, which regulates the provision of business and investment guarantees as the outcome of policy implementation. The policy on blockchain must formulate norms that guarantee the determination of the legal status of land owners of land right and interested parties.